2019
DOI: 10.1103/physrevb.100.045141
|View full text |Cite
|
Sign up to set email alerts
|

Topological phase transition independent of system non-Hermiticity

Abstract: Non-Hermiticity can vary the topology of system, induce topological phase transition, and even invalidate the conventional bulk-boundary correspondence. Here, we show the introducing of non-Hermiticity without affecting the topological properties of the original chiral symmetric Hermitian systems. Conventional bulk-boundary correspondence holds, topological phase transition and the (non)existence of edge states are unchanged even though the energy bands are inseparable due to non-Hermitian phase transition. Ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 170 publications
(196 reference statements)
0
24
0
Order By: Relevance
“…In the topological classification discussed in Refs. [36], the NH chiral-symmetric Hamiltonians are discussed and the topological invariant and bulk-boundary correspondence has been established [36,71]. They can also be considered in the framework of pseudo-Hermitian Hamiltonians because iH k is a pseudo-Hermitian matrix.…”
mentioning
confidence: 99%
“…In the topological classification discussed in Refs. [36], the NH chiral-symmetric Hamiltonians are discussed and the topological invariant and bulk-boundary correspondence has been established [36,71]. They can also be considered in the framework of pseudo-Hermitian Hamiltonians because iH k is a pseudo-Hermitian matrix.…”
mentioning
confidence: 99%
“…The linking number associated with this phase is L = 0 and the band is topologically trivial. Notably, the anti-PT -symmetric coupling induces the topological phase transition at the EP, which dramatically differs from the topological phase transitions in other non-Hermitian systems with PTsymmetric gain and loss [28][29][30][31][32][33][34], as well as in non-Hermitian systems with asymmetric coupling strengths [54][55][56][57][58][59], where topological phase transition is irrelevant to the EP. Counterintuitively, increasing the dissipation can create nontrivial topology instead of behaving destructively: more dissipation reduces the strength of the anti-PT -symmetric coupling, tying vector field link and increasing the linking number.…”
Section: Linking Topologymentioning
confidence: 76%
“…Photonic crystal is an excellent platform for the study of topological physics [6]. The non-Hermitian quasicrystal [21,22], high-order topological phase [23][24][25][26][27], robust edge state [28][29][30][31][32][33][34][35][36], and topological lasing [37][38][39][40][41][42][43] in photonic crystals were discovered. Here, we consider a photonic crystal lattice as schematically illustrated in Fig.…”
Section: Dissipative Photonic Crystal Latticementioning
confidence: 99%
“…[ 18 ] It was found that non‐Hermitian Aharonov–Bohm effect is essential for the validation of conventional bulk‐boundary correspondence in non‐Hermitian realm, and the inversion or combined inversion symmetry is critical for restoring conventional bulk‐boundary correspondence. [ 40–42 ] The topology of real‐energy gapless phase resulting from exceptional point has been discussed in ref. [43].…”
Section: Introductionmentioning
confidence: 99%